Treatment with the CCR5 antagonist OB-002 reduces lung pathology, but does not prevent disease in a Syrian hamster model of SARS-CoV-2 infection. - Bryce M Warner; Robert Vendramelli; Amrit S Boese; Jonathan Audet; Nikesh Tailor; Courtney Meilleur; Nathan Glowach; Marnie Willman; Thang Truong; Estella Moffat; Kevin Tierney; Beata Kosak; et al. (PLoS ONE)
Since the emergence of SARS-CoV-2 and the COVID-19 pandemic, a wide range of treatment options have been evaluated in preclinical studies and clinical trials, with several being approved for use in humans. Immunomodulatory drugs have shown success in dampening the deleterious inflammatory response seen in severe COVID-19 patients, but there remains an urgent need for development of additional therapeutic options for COVID-19 treatment. A potential drug target is the CCR5-CCL5 axis, and blocking this pathway may protect against severe disease. Here we evaluated whether OB-002, an analog of human CCL5 and a potent antagonist of CCR5, provides therapeutic benefit in SARS-CoV-2 infected Syrian hamsters. Daily treatment with OB-002 altered immune gene transcription in the lungs, and reduced pathology following infection, but did not prevent weight loss or viral replication in the lungs of infected animals, even in combination with the antiviral drug remdesivir. Our data suggest that targeting the CCR5-CCL5 pathway in SARS-CoV-2 infection in hamsters is insufficient to significantly impact disease development in this model.